Luaran Pendekatan Operasi Mikroskopis dan Endoskopik pada Pasien Kraniofaringioma di RSUPN Dr. Cipto Mangunkusumo - Ashari, Samsul; Saekhu, Mohamad; Tandian, David; Ray, Laode Maly; Nugroho, Setyo Widi (PERDOSNI, 2023)
ABSTRACTIntroduction: Advances in neurosurgery technology are rising quickly. The Neurosurgery Department RSCM is currently developing minimally invasive surgical technique using transcranial endoscopy. This minimally invasive procedure have been carried out to date. However, the patient's outcome after surgery is not yet known.Aim: Acknowledging the outcome of microscopic and endoscopic surgical approaches in craniopharyngioma patients at dr. Cipto Mangunkusumo Hospital.Methods: This was a retrospective cohort study of craniopharyngioma patients who underwent either endoscopic or microscopic surgery. This study used a consecutive sampling technique, using samples from 2012 to 2021 at Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia. The inclusion criteria were craniopharyngioma patients who were admitted to the hospital for craniotomy tumor removal procedure with an endoscopic or microscopic approach, never had surgery, had diagnosis of craniopharyngioma confirmed by clinical findings and supporting investigation. Exclusion criteria were patients with extracranial problems and endoscopic patients with extensive craniotomy. Demographic data such as age, gender, tumor location, consistency, anatomical pathology results, and history of radiotherapy were recorded. Clinical outcomes were pre- and postoperative complaints, intraoperative bleeding, postoperative complications, and recurrence. Resectability is the size of the tumor pre- and 1-month after surgery. The data were analyzed using SPSS 25.0.Results: Thirty patients were enrolled in this study. A total of 22 subjects (73%) underwent microscopic surgery and 8 subjects (27%) underwent endoscopic surgery. Intraoperative bleeding was found to be significantly smaller on the endoscopic approach than on the microscopic approach (p=0.002). The operation time of endoscopic approach was significantly shorter than microscopic approach (p=0.002). There was no significant difference in pre- and postoperative complaints, postoperative complications, recurrence, resectability and duration of hospitalization in the endoscopic approach compared to the microscopic approach in the management of craniopharyngioma patients.Conclusion: Transcranial endoscopic approach in craniopharyngioma patients has good potential as an option for surgical management of craniopharyngioma patients.Keywords: Craniopharyngioma, Transcranial Endoscopy, Microscopy